Tradições orais e ensino de História na escola Professora Carmina Gomes, no ensino fundamental II, em São Félix do Xingu - Pará - Santos, Joelma da Silva (Universidade Federal do Tocantins, 2020)
This work aims to present a methodology of oral history teaching, using one of its genres, oral traditions, since many stories that are part of the social imaginary are counted, but are not recorded. When working with orality memory is very important. According to Le Goff (2014), in the study of historical memory it is necessary to give special importance to differences for oral, written, or transitional societies from oral to written. The research involved the students of the 7th grade of the Carmina Gomes Teacher School in São Félix do Xingu. We work with orality, from local legends, through interviews and collection of narratives, as a way to contribute to a teaching of History with more meaning, since this study starts from the local and the daily life of the student, and still allows the use of a methodology that goes beyond the walls of the school. The oral history worked here does not have the objective of strict analysis of the narratives, but rather of allowing students different forms of remembrance and historical transmission, respect for cultural diversity and recognition that history also happens in their place of living, with several historical subjects. As a result of the research, there is the preparation, together with the students, of a booklet of Stories from the narratives of the older residents of the city of São Félix do Xingu.